DEVELOPING A CLIENT-SERVER APPLICATION FOR SELECTING AN EMPLOYEE ON THE ANDROID PLATFORM - Uzakbayev, Н; Yerekesheva, М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Android is a relatively new operating system that has become very popular in the mobile device market in a short time. Operating system developers must adhere to the following basic requirements: the new platform must be based on open standards, which will reduce development costs and provide mobile application developers with access to all system functions to create applications. One of the main advantages of the Android platform is its transparency. The Android operating system is open source and free. This allows users to access the source code and understand how application properties and functions are implemented. This article describes the software, structure, functionality, and scope of the client-server application for personnel selection created on the Android platform.